The relationship between cervical proprioception and concussion in male professional rugby players - Farley, T.; Bester, K.; Barbero, A.; Barry, E.; Thoroughgood, J.; Sylvester, R.; Medici, A.; Wilson, M. (British Journal of Sports Medicine, 2021)
Background During a tackle 1997 Newtons of force (equivalent to 204kg) is known to be transmitted to an opponent, however there is currently no known minimal force threshold leading to concussion. Amongst the other factors considered, contact technique has been identified as a potential injury cause, with head position proposed as a key variable.